2014
DOI: 10.1371/journal.pone.0109561
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predisposing to Maxillary Anchorage Loss: A Retrospective Study of 1403 Cases

Abstract: Anchorage loss is very disturbing for orthodontists and patients during orthodontic treatment, which usually results in bad treatment effects. Despite the same treatment strategy, different patients show different tendencies toward anchorage loss, which influences the treatment results and should preferably be predicted before the treatment is begun. However, relatively little research has been conducted on which patients are more likely to lose anchorage. The mesial tipping of the first molar marks the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…In delayed extraction dental cast distance of point According to the study done by Su et al maxillary first molars have tendency to tip mesially, and if the molars are distally tipped before treatment, the more they will tip mesially during treatment. 18 Moreover, mesial movement of first maxillary molar during orthodontic treatment is seen more commonly in class II malocclusion and in the premolar extraction cases.…”
Section: Discussionmentioning
confidence: 99%
“…In delayed extraction dental cast distance of point According to the study done by Su et al maxillary first molars have tendency to tip mesially, and if the molars are distally tipped before treatment, the more they will tip mesially during treatment. 18 Moreover, mesial movement of first maxillary molar during orthodontic treatment is seen more commonly in class II malocclusion and in the premolar extraction cases.…”
Section: Discussionmentioning
confidence: 99%
“…1 Anchorage loss is an unfortunate consequence of leveling and aligning, overjet reduction or space closure and is usually greater in the maxillary than mandibular arch. 2 This complicates treatment, and when anchorage preparation is not adequately planned, molar distalization may be required during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment-related factors, such as extractions versus non-extraction, site of extraction, high frictional resistance appliances, type of tooth movement (bodily movement or torque), the use of intraoral or extra-oral anchorage devices and the use of heavy and uncontrolled forces can also play a role in increasing anchorage loss. 2,3 Anchorage loss has been investigated with different orthodontic fixed appliance systems. In their retrospective study, Geron et al 3 found that anchorage loss was significantly greater with labial edgewise appliances compared with lingual edgewise appliances.…”
Section: Introductionmentioning
confidence: 99%
“…In orthodontic treatment, undesirable tooth movement of the anchorage unit and the relapse of moved teeth to their original positions are important problems [1,2]. Various mechanical appliances have been used to reinforce the anchorage in such cases, such as the transpalatal arch, Nance holding arch, temporary anchorage device, and headgear.…”
Section: Introductionmentioning
confidence: 99%